Analisis Kinerja Pelayanan Operasional Terminal II Pelabuhan Petikemas New Makassar - Riska Damayanti; Andi Sitti Chairunnisa; Esther Sanda Manapa (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Ports influence local economic development and facilitate the flow of commodity distribution between regions. Ports become drivers of regional development supported by optimal logistics system performance. Seeing the importance of maritime logistics in Indonesia, it is necessary to build a comprehensive maritime logistics system with good performance. One of the ports that can be an illustration of the condition of ports in Indonesia is Terminal II of the New Makassar Container Port where this port is designated as the main port of Makassar city which supports export-import activities. Thus, this study aims to analyze the service performance of Terminal II operational activities. The method used is through observation or direct visits to research locations to obtain data related to operational performance and conduct analysis by comparing performance achievements with predetermined performance standards. Based on the results of the analysis that has been carried out, the overall operational service performance results are stated to be good because they comply with performance standards. However, the obstacle in increasing the flow of containers to support performance is the lack of international ships mooring due to the limited length of the berth being operated.